2018
DOI: 10.1002/zamm.201700097
|View full text |Cite
|
Sign up to set email alerts
|

Forced vibrations of nonlinear symmetrical and asymmetrical rotating shafts mounted on a moving base

Abstract: This paper deals with the combinational resonances of symmetrical and asymmetrical rotating shafts with base motions. The nonlinearities are owing to the large amplitude of the hinged‐ hinged the shaft. Generally, the asymmetrical shaft has unequal principal mass moments of inertia and flexural stiffnesses. The system is exposed to three sources of excitation as a result of the asymmetry of the shaft, dynamic imbalances, and base excitations. Using the variational approach the nonlinear governing equations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…One-mode discretization is performed in this section. The following expression is assumed for spatial form of the response [20,22]:…”
Section: One-mode Discretization Combination Resonance Of Typementioning
confidence: 99%
See 1 more Smart Citation
“…One-mode discretization is performed in this section. The following expression is assumed for spatial form of the response [20,22]:…”
Section: One-mode Discretization Combination Resonance Of Typementioning
confidence: 99%
“…Their results showed that the parametric excitation could be used to control the vibration. Shahgholi and Payganeh [22] studied the combination resonances of an asymmetrical metallic spinning shaft having moving base using the method of multiple scales. There were three excitations in their research which were due to imbalances, asymmetry, and base movement.…”
Section: Introductionmentioning
confidence: 99%
“…Other contributions were devoted to onboard rotors with geometric nonlinearities caused by large shaft displacements. This was the case of Phadatare et al [18] with their highly flexible shaft mounted on a base subject to sinusoidal vertical translations and of Shahgholi et al [19] with their asymmetric shaft whose support was subject to sinusoidal transverse rotations. In both these works, the shaft dynamics was restricted to the first mode of the linear system to facilitate the application of perturbation methods.…”
Section: Introductionmentioning
confidence: 99%
“…To be more precise, in isotropic case: Hosseini and coworkers studied different aspects of nonlinear rotating shafts . Shahgholi and Payganeh analyzed the symmetrical and asymmetrical rotating shafts mounted on a moving base.…”
Section: Introductionmentioning
confidence: 99%